35 years of socially responsible investing (SRI) research: General trends over time - S. Viviers; N. S. Eccles (South African Journal of Business Management, 2012)
This article describes 35 years of academic research into investment practices that in some way integrate a consideration of environmental, social and corporate governance Issues. A review of 190 academic papers was undertaken to identify trends in five domains, namely `Primary Name', `Research Themes', `Ethical Foundations', `Research Approach' and `SRI Strategies'. The evidence reveals that more than half the researchers refer to such investment practices as Socially Responsible Investing (SRI) and for this reason the name is used in this review as a generic term for the genre. A myriad of other names were also identified. In terms of research themes, one particularly dominant theme was that of financial performance, which was often discussed in relation to fiduciary responsibility and legal aspects. Although the primary ethical foundation was not always directly observable, the majority of papers implied utilitarianism or `the greatest good for the greatest number'. Increased mention of ethical egoism (self-interest) is observed in later periods. An equal split between qualitative and quantitative research methodologies was noted, with a qualitative approach being more favoured in recent years. Three SRI strategies have dominated academic discussions over the past 35 years, namely negative screening, positive screening and shareholder activism. Gaps in the literature have been identified and suggestions for future research made.
Keywords: 650